A Suggested Educational Guide to Enhance the Role of Jordanian Universities in Developing Moderate Thinking among their Students, Based on the Amman Message - Al-Aifan, Reem Mishref; Al-Qudah, Muhammad Amin (Dirasat: Educational Sciences, 2022)
Objectives: The study aimed to propose an educational guide for Jordanian universities to enhance their role in developing moderate thought among their students based on the Amman Message, by identifying the reality of the role of Jordanian universities in developing moderate thought based on the Amman Message from the viewpoint of faculty members. Methods: The study used the (qualitative) method in collecting data from the study sample, revealing the role of Jordanian universities in promoting and developing moderate thinking. The study sample consisted of faculty members in Jordanian public universities for the academic year 2019/2020, where the study sample consisted of (20) faculty members in Jordanian universities, and data was collected through conducting interviews. Results: The results of the qualitative study showed agreement of 90% of the study sample on The middle thought is the moderate thought. And that moderate thought immunizes students from extremism and leniency at the same time, and that the promotion of moderate thought is through academic courses and the university professor, and 70% of the sample indicated the spread of moderate thought among students and in light of the results of the current qualitative study and a previous quantitative study that was published in a research. Conclusions: An independent educational guide has been proposed to enhance the role of Jordanian universities in developing moderate thought based on the Amman Message, which the study recommended to adopt, to help universities develop moderate and moderate thought, and to activate their role more through the elements of the educational process.